Aplikasi Petrologi Organik Dalam Analisis Cekungan dan Eksplorasi Hidrokarbon pada Beberapa Cekungan di Indonesia dan Australia - Asep Kurnia Permana (Pusat Survei Geologi, 2017)
The organic petrology is useful in many aspects of geological applications. This method is mainly applied for geoscience investigation, such as basin analysis, fossil fuel resources exploration, and coal utilization. In the last few years, organic petrology has been applied in other fields such as environmental, archeology, and forensic studies. Study of organic petrology and its applications have also been applied in some Indonesian and Australian Basins. The organic petrography method was combined with other analytical techniques to get comprehensive results, for instance Scanning Electron Microscope (SEM), Palynology, Rock-Eval Pyrolysis, Gas Chromatography-Mass Spectrometry (GC-MS), X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), and Microfocus X-Ray Tomography. Combination of those analytical techniques have been widely used for identification and characterization of organic matter and mineral matter association, even more quantification as well as assessment of the maturity level and rank of organic matter in the organic rich sediments. This paper provides a review of the organic petrology application in basin analysis and hydrocarbon exploration. This research is focused on application of Organic petrology for reconstruction of paleoenvironment, geological history, hydrocarbon source rocks, and unconventional hydrocarbon potential in some Indonesian and Australian Basins. Keyword: organic petrology, basin analysis, hydrocarbon exploration